2019
DOI: 10.1111/opo.12600
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and conjunctival injury seen in urgent care centres in Israel

Abstract: PurposeCorneal and conjunctival injuries (CCI) comprise a large portion of the cases presenting to hospital‐based emergency departments (ED) with ocular involvement. Urgent Care Centres (UCC) offer community based emergency care at lower cost than hospital‐based emergency departments (ED) and with greater temporal convenience than primary care office settings. While CCI prevalence and treatment at hospital‐based EDs has been well studied, this is the first report, to our knowledge, on CCI demographics and aeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…The percentage of both injuries is higher than the percentage that Fea et al obtained in their 2008 study in an urgent care department in Torino, with 44.18% of the eye injuries classified as corneal damage and 10.03% as conjunctivitis [3]. Our results also show differences with the results of the recent study of Zimmerman et al in Israel [14]. Both studies were carried out in urgent care departments, so they studied the general population as well as workers.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The percentage of both injuries is higher than the percentage that Fea et al obtained in their 2008 study in an urgent care department in Torino, with 44.18% of the eye injuries classified as corneal damage and 10.03% as conjunctivitis [3]. Our results also show differences with the results of the recent study of Zimmerman et al in Israel [14]. Both studies were carried out in urgent care departments, so they studied the general population as well as workers.…”
Section: Discussioncontrasting
confidence: 94%
“…In all risk factors analyzed (sex, age, and occupation), injuries with a higher number of cases and percentage were the keratitis and conjunctivitis incidences. The higher number of cases in males has been associated by some authors with a higher exposition due to the occupation they have [8,10,14,17,21]. In our study, males have a higher RR and had a higher percentage of keratitis incidences (p < 0.001), which comes from the damage of the cornea, which is the most exposed eye structure to risk factors associated with the occupation.…”
Section: Discussionsupporting
confidence: 54%
“…An ocular surface foreign body is an object such as glass, metal, or sand, which gets adhered to or embedded into different ocular surfaces 11 . These are commonly found in cornea and palpebral Conjunctival surfaces 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that the use of PG can protect most of the workers from CFB trauma, as well as from possible scarring in the cornea (1). It has also been shown that leaving the CFB for more than 24 hours causes the rust ring to result in a corneal scar eventually (7).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal foreign body (CFB) trauma is a common eye injury in the emergency departments (ED) (1). The CFB trauma is mostly associated with occupational accidents frequently seen in construction and metal industry workers (2).…”
Section: Introductionmentioning
confidence: 99%